1998
DOI: 10.1093/hmg/7.11.1703
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Myotubularin Dual Specificity Phosphatase Gene Family from Yeast to Human

Abstract: X-linked myotubular myopathy (XLMTM) is a severe congenital muscle disorder due to mutations in the MTM1 gene. The corresponding protein, myotubularin, contains the consensus active site of tyrosine phosphatases (PTP) but otherwise shows no homology to other phosphatases. Myotubularin is able to hydrolyze a synthetic analogue of tyrosine phosphate, in a reaction inhibited by orthovanadate, and was recently shown to act on both phosphotyrosine and phosphoserine. This gene is conserved down to yeast and strong h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
101
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(103 citation statements)
references
References 34 publications
2
101
0
Order By: Relevance
“…To this end, we have expressed recombinant human myotubularin in E. coli as a fusion protein (GST-MTM1-His 6 ) with N-terminal glutathione S-transferase and C-terminal six-histidine tags for affinity purification. As previously shown, the recombinant myotubularin fusion protein is active toward the artificial PTP substrate para-nitrophenylphosphate (pNPP) (8). We have found that myotubularin hydrolyzes pNPP at a pH optimum of 6.0 with a K m of 21 mM, a k cat of 0.4 s Ϫ1 , and a k cat ͞K m of 20 s Ϫ1 ⅐M Ϫ1 .…”
Section: Recombinant Myotubularin Is a Highly Efficient Pi(3)p Phosphmentioning
confidence: 82%
See 2 more Smart Citations
“…To this end, we have expressed recombinant human myotubularin in E. coli as a fusion protein (GST-MTM1-His 6 ) with N-terminal glutathione S-transferase and C-terminal six-histidine tags for affinity purification. As previously shown, the recombinant myotubularin fusion protein is active toward the artificial PTP substrate para-nitrophenylphosphate (pNPP) (8). We have found that myotubularin hydrolyzes pNPP at a pH optimum of 6.0 with a K m of 21 mM, a k cat of 0.4 s Ϫ1 , and a k cat ͞K m of 20 s Ϫ1 ⅐M Ϫ1 .…”
Section: Recombinant Myotubularin Is a Highly Efficient Pi(3)p Phosphmentioning
confidence: 82%
“…Although previous studies have demonstrated that recombinant myotubularin possesses dual specificity protein phosphatase activity, its relative efficiency toward these substrates has not been reported (7,8). To this end, we have expressed recombinant human myotubularin in E. coli as a fusion protein (GST-MTM1-His 6 ) with N-terminal glutathione S-transferase and C-terminal six-histidine tags for affinity purification.…”
Section: Recombinant Myotubularin Is a Highly Efficient Pi(3)p Phosphmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, MTM1 was reported to be a dual-specificity phosphatase (4)(5)(6). However, we and others have demonstrated that MTM1 utilizes the lipid second messenger, phosphatidylinositol 3-phosphate [PI(3)P], as a physiological substrate (7,8).…”
mentioning
confidence: 99%
“…Type 4B1 Charcot-Marie-Tooth disease is an autosomal recessive demyelinating neuropathy characterized by abnormally folded myelin sheaths and Schwann cell proliferation in peripheral nerves (23,24). MTM1 and MTMR2 are highly similar proteins (64% identity, 76% similarity), use the same physiologic substrate, and have a ubiquitous expression pattern (6,(9)(10)(11)(12). However, mutations in MTM1 and MTMR2 cause different diseases with different target tissues and pathological characteristics.…”
mentioning
confidence: 99%